2017
DOI: 10.5301/ijao.5000587
|View full text |Cite
|
Sign up to set email alerts
|

Infection in Critically Ill Pediatric Patients on Continuous Renal Replacement Therapy

Abstract: Infection rate is high in critically ill children treated with CRRT. More than 4 days of CRRT increases the risk of infection. Infection in these patients entails a longer stay in the PICU but did not increase mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Critically ill patients with AKI treated with KRT are more susceptible to a nosocomial bloodstream infection, most commonly caused by Gram-positive species [ 92 ]. Similar findings were also observed in critically ill children treated with CKRT, demonstrating that more than four days of CKRT increased the risk of infection [ 93 ].…”
Section: Pathophysiology Of Sepsis Following Akisupporting
confidence: 73%
“…Critically ill patients with AKI treated with KRT are more susceptible to a nosocomial bloodstream infection, most commonly caused by Gram-positive species [ 92 ]. Similar findings were also observed in critically ill children treated with CKRT, demonstrating that more than four days of CKRT increased the risk of infection [ 93 ].…”
Section: Pathophysiology Of Sepsis Following Akisupporting
confidence: 73%
“…While the difference in survival did not achieve statistical significance, we observed a trend towards decreased survival rates amongst patients who were immunocompromised. There is very limited pharmacokinetic data in pediatric CRRT, potentially impacting optimal treatment of CRRT patients particularly with antimicrobials, as pediatric CRRT patients are reported to have increased infections [ 42 ]. Further study is warranted to determine if higher infection susceptibility translates to increased morbidity from suboptimal treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In a single center retrospective cohort study, a higher odds of infection in a single center study of 5,000 critically ill children: there was a non-linear increase in risk for sepsis based on AKI severity, with stage 3 AKI patients incurring the greatest risk for sepsis ( 99 ). A small single center study of pediatric patients receiving CRRT also found an association with infection, that occurred a median of 11 days after CRRT initiation ( 101 ).…”
Section: Aki and The Effects On Other Organ Systemsmentioning
confidence: 99%